Brake body for motor vehicle
By using iron alloy matrix composite materials embedded in tungsten carbide or titanium carbide particles on the motor vehicle brake as the second and secondary construction layers through molybdenum alloy, the corrosion and wear of the brake body can be solved The problem realizes higher wear resistance and lower dust emissions.
Patent Information
- Application Number
- CN202410988346.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-24
- Filing Date
- 2024-07-23
- Publication Date
- 2025-01-24
AI Technical Summary
Due to the high corrosion tendency of materials and friction wear, existing motor vehicle brake bodies lead to early damage and fine dust emissions, and it is difficult to effectively prevent cracking.
The composite material composed of iron alloy matrix with an embedded tungsten carbide or titanium carbide particles is used as the second constructing layer of the brake body, and the first and second layers are improved through molybdenum alloy.
It significantly reduces the tendency and cracking tendency of the brake body, improves wear resistance and friction performance, reduces dust emissions, and prolongs the service life of the brake.
Smart Images

Figure CN119353337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a brake body for a motor vehicle. Background Art
[0002] Braking bodies, such as brake discs or brake disc friction rings, are usually made of grey cast iron. The advantages of grey cast iron, in particular the high volumetric heat capacity and the relative resistance to thermal shock, are offset by various disadvantages. These disadvantages include high weight, a strong tendency to corrosion and high material wear during operation of the motor vehicle.
[0003] The corrosion causes visual defects, since the brake body is the only component of the motor vehicle that has developed red rust after a short period of time. In addition, due to the frequently used open aluminum rims, the brake disc is directly visible.
[0004] In the case of a frugal driving style or in the case of high recuperation rates (when braking occurs only rarely), the tendency of the material to corrode can lead to such extensive damage to the brake element that it must be replaced at an early stage.
[0005] Furthermore, the frictional wear of the brake bodies leads to the emission of fine dust, the amount of which can significantly exceed the fine dust emissions of modern internal combustion engines.
[0006] In order to eliminate these disadvantages, it has hitherto been known that, in addition to completely replacing the material of the brake body by a hard and corrosion-resistant material such as ceramic, the friction surface of the brake body can also be protected by means of suitable coatings.
[0007] There are therefore various approaches to coating, in particular for particularly stressed friction surfaces of brake bodies, which are used for combined wear and corrosion protection. The coating is carried out by thermal spraying methods for applying oxide ceramic or hard material-containing coatings. Thus, various coating materials based on metal alloys or composite materials consisting of ceramic particles or hard metal particles in a metal matrix are used, which offer improved behavior with respect to corrosion and wear.
[0008] As the thermal spraying method, for example, high-speed slurry spraying, plasma spraying, cold gas spraying or arc wire spraying can be cited.
[0009] DE 10 2021 207 133 B3 of the applicant discloses a brake body for a motor vehicle. Specifically, in order to increase the wear resistance and to reduce the tendency to cracking in the building layer, it is proposed that the first building layer has a thickness in the range of 40 to 120 microns and the second building layer has a thickness in the range of 60 to 420 microns. In this case, the second building layer consists of a composite material consisting of an iron alloy matrix with embedded tungsten carbide particles, wherein the volume of the embedded tungsten carbide particles accounts for a proportion of the volume of the iron alloy matrix in the range of 20% to 40%.
[0010] EP 3 325 685 B1 of the applicant describes a cylinder crankcase with a coated cylinder running surface. The coating of the cylinder running surface has a mixed layer, which is composed of a base material and an adhesion promoter. A layer of base material is applied to the mixed layer. The base material is iron or an iron alloy, while the adhesion promoter contains a mixture of 20 to 80 weight percent molybdenum and 20 to 80 weight percent aluminum-containing alloy. Summary of the invention
[0011] The invention is based on the object of providing a brake body for a motor vehicle which has improved properties with regard to wear resistance and cracking tendency.
[0012] This object is achieved by the brake body according to the invention. Advantageous embodiments or developments of the invention can be derived from the invention.
[0013] The invention is based on a brake body for a motor vehicle, which has a base body which is at least partially flat, to the flat sides of which at least two buildup layers are respectively applied at least partially. The buildup layers form a surface which, in the assembled state of the brake body mounted on the motor vehicle, serves as a friction surface for a brake lining. There is a first buildup layer which adjoins the base body. A second buildup layer is applied to the first buildup layer, wherein the second buildup layer consists of a composite material consisting of an iron alloy matrix with embedded tungsten carbide particles or with embedded titanium carbide particles.
[0014] According to the invention, at least the first building layer is an iron alloy that is alloyed (or admixed, i.e., auflegiert) with at least molybdenum (Mo) in a range of about 3 weight percent to about 20 weight percent, preferably in a range of about 3 weight percent to about 12 weight percent. The first building layer is particularly preferably alloyed with molybdenum in a range of about 10 weight percent. In other words, the mass proportion of alloyed molybdenum in the total mass of the first building layer is in a range of about 3% to about 20%.
[0015] According to a first advantageous development of the invention, it is provided that the second structured layer is also alloyed with molybdenum at least in a range of 3 weight percent to 20 weight percent, preferably in a range of about 3 weight percent to about 12 weight percent. The second structured layer is particularly preferably alloyed with molybdenum to a level of about 10 weight percent.
[0016] In this way, the tendency of the brake disk to wear and crack can be further reduced.
[0017] According to another refinement of the invention, when a composite material consisting of an iron alloy matrix with embedded tungsten carbide particles is present in the second building layer, the volume of the embedded tungsten carbide particles accounts for a proportion of the volume of the iron alloy matrix in the range of about 10% to about 20%.
[0018] In the case where a composite material consisting of an iron alloy matrix with embedded titanium carbide particles is present in the second building layer, according to one refinement, the volume of the embedded titanium carbide particles accounts for a proportion of the volume of the iron alloy matrix in a range of about 10% to about 40%, preferably in a range of about 15% to about 30% and particularly preferably about 20%.
[0019] The above-mentioned volume distribution can further reduce the tendency to crack, in particular in the second building layer, wherein high wear resistance and good friction values can be achieved when using brake elements.
[0020] According to another advantageous embodiment of the invention, the first building layer consists of austenitic stainless steel having material properties corresponding to material 1.4404 according to DIN EN 10027-2 or material 316L according to AISI.
[0021] However, depending on the material properties of the base body of the brake body, it is alternatively conceivable and has proven to be advantageous for the first building layer to consist of a ferritic stainless steel having material properties corresponding to 1.4016 material according to DIN EN 10027-2 or 430L material according to AISI.
[0022] By means of the above-mentioned alternatives, the first building layer can be optimally matched to the respective material properties of the base body, in particular with regard to its coefficient of thermal expansion.
[0023] The brake body can be improved in that the first structured layer, viewed perpendicularly to the planar extension of the planar side, has a thickness in the range from approximately 50 μm to approximately 350 μm.
[0024] According to another development of the invention, the second structured layer has a thickness in the range of approximately 60 μm to approximately 420 μm, viewed perpendicularly to the planar extension of the planar side.
[0025] Another advantageous embodiment of the present invention provides that the iron alloy matrix in the second construction layer consists of a material having material properties corresponding to the 1.4404 material according to DIN EN 10027-2 or the 316L material according to AISI. This embodiment is particularly suitable when the first construction layer has such a material.
[0026] Alternatively, according to another improvement, the iron alloy matrix in the second building layer is composed of a material having material properties corresponding to 1.4016 material according to DIN EN 10027-2 or 430L material according to AISI standard. This configuration is particularly suitable when the first building layer has such a material.
[0027] This development can contribute to better adhesion of the second building layer if the iron alloy in the first building layer is selected accordingly.
[0028] Preferred embodiments of the present invention are shown in the accompanying drawings and explained in more detail in the following description with the aid of the accompanying drawings. This also makes other features and advantages of the present invention clearer. Even in different drawings, the same reference numerals also relate to the same, comparable or functionally identical components. Here, even if repeated description or reference is not performed, the corresponding or comparable characteristics and advantages are achieved. The accompanying drawings are not or at least not always in correct proportion. In some drawings, the proportions or distances may be exaggeratedly presented so that the features of the embodiments can be emphasized more clearly. If the term "and / or" is used when listing two or more terms or objects, this may mean: any one of the terms or objects listed can be used alone. It can also mean that any combination of two or more listed terms or objects can be used. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Schematically shown respectively:
[0030] Figure 1 A motor vehicle is shown with a brake body according to the invention;
[0031] Figure 2 A cross section of a brake body is shown in a single illustration;
[0032] Figure 3 Show according to Figure 2 Detail of Detail III; and
[0033] Figure 4 The diagram shows the process steps in a method for producing a brake body. DETAILED DESCRIPTION
[0034] First reference Figure 1 . In this figure, a motor vehicle K equipped with a brake body 1 according to the invention can be seen. The brake body 1 is designed as a disk brake and is mounted on a wheel carrier (not shown in detail) so as to be rotatable about an axis of rotation R. The brake calipers 2 each contain an advanceable brake lining (not shown), for which the brake body 1 forms a friction surface via its brake disk friction ring. When the brake lining is pressed against the friction surface of the brake body 1, the motor vehicle K is braked or stopped.
[0035] exist Figure 2 , the brake body 1 is shown in a single illustration and in a cross-sectional view. The brake body 1 rotates about an imaginary axis of rotation R. For reasons of rotational symmetry, only half of the brake body 1 is shown.
[0036] It can be seen that the brake body 1 is constructed as a brake disc ventilated on the inside in this embodiment, which has two friction rings 10a and 10b. In contrast to the embodiment, a brake disc with only one friction ring is also conceivable. A ventilated intermediate space 11 is located between the friction rings 10a, 10b. The necessary spacing ribs between the friction rings 10a, 10b are not shown. Each friction ring 10a, 10b has a flat base body G with a flat side Fa or Fb. Each flat side Fa, Fb has a flat extension F and is provided with a coating B. The friction surface 12 that acts during braking is respectively constructed by the coating B.
[0037] In this exemplary embodiment, the coating B extends over the entire flat side Fa or Fb of the base body G. Deviating therefrom, it is also conceivable that the coating B is applied only to that region of the flat side Fa, Fb which is swept over by the brake lining.
[0038] The hub of the brake body 1 is designated by 13 and is used for mounting the brake body 1 on a wheel carrier (not shown).
[0039] Now from Figure 3 Detailed areas of the cross section of the brake body 1 can be seen in FIG. In particular, it can be seen that the coating B consists of a first building layer B1 and a second building layer B2.
[0040] The first building layer B1 is applied directly to the base body G, ie directly adjoins said base body G. The second building layer B2 is in turn applied to the first building layer B1.
[0041] It can be seen here that the first building layer B1 has a thickness d1 perpendicular to the planar extension F of the planar side Fa (or Fb). The thickness d1 is preferably in the range of about 50 micrometers to about 350 micrometers.
[0042] In contrast, the second building layer B2 has a thickness d2 which is preferably between approximately 60 micrometers and approximately 420 micrometers.
[0043] By means of these layer thickness ranges, the objectives of the first building layer B1 for the corrosion protection and the suppression of cracks from the second building layer B2 can be optimally met.
[0044] The specified thickness range of the second building layer B2 meets the requirements of high wear resistance, whereby particle emissions resulting from frictional wear can be significantly reduced.
[0045] Furthermore, a mixing or bonding zone A is outlined, which is located in the transition between the base body G and the adjoining first building layer B1. The bonding zone A is characterized in that a certain mixing occurs here between the material of the base body G and the material of the coating B1. The bonding zone A has a thickness d3 perpendicular to the plane extension F, which is only very thin and is less than 10 micrometers. Preferably, the bonding zone A has a thickness d3 which is less than 5 micrometers.
[0046] It has been shown that, by such a small thickness of the bonding zone A, on the one hand, grain formation and hardening of the first structured layer B1 can be prevented, while on the other hand, good adhesion of the first structured layer B1 to the base body G can still be achieved. Adhesion tensile strengths far exceeding 50 MPa can be achieved. This provides the basic prerequisite for high wear resistance and high corrosion protection.
[0047] The materials used will now be discussed in detail below. Thus, the base body G is made of grey cast iron. The base body together with the hub 13 (see Figure 2 ) are made together using common casting methods.
[0048] The first building layer B1 consists of an iron alloy, preferably of austenitic stainless steel, which is a particularly ductile and tough iron alloy. The material of the first building layer B1 particularly preferably has material properties corresponding to 1.4404 material according to DIN EN 10027-2 or 316L material according to AISI standard.
[0049] Furthermore, as an important feature, the iron alloy in the first building layer B1 is alloyed with molybdenum. The alloying is in the range of about 3 weight percent to 20 weight percent, preferably in the range of about 3 weight percent to 12 weight percent. Particularly preferably, the first building layer B1 is alloyed with molybdenum at a level of about 10 weight percent. In other words, the mass proportion of alloyed molybdenum in the total mass of the first building layer B1 is in the range of about 3% to about 20%.
[0050] However, it is also conceivable that the iron alloy in the first building layer B1 consists of ferritic stainless steel. The ferritic stainless steel may preferably have material properties corresponding to 1.4016 material according to DIN EN 10027-2 or 430L material according to AISI standard. In this case, however, as an important feature, the iron alloy in the first building layer B1 is also alloyed with molybdenum in the same manner as described above.
[0051] The second building layer B2 consists of a composite material consisting of an iron alloy matrix E with embedded tungsten carbide particles W. It has proven to be particularly advantageous if the volume of the embedded tungsten carbide particles W in the second building layer B2 accounts for a proportion of the volume of the iron alloy matrix E in the range of about 10% to about 20%.
[0052] As an alternative, it is conceivable that the second building layer B2 consists of a composite material consisting of an iron alloy matrix E with embedded titanium carbide particles T. In this case, it has proven to be particularly advantageous if the volume of the embedded titanium carbide particles T in the second building layer B2 accounts for a proportion of the volume of the iron alloy matrix E in the range from about 10% to about 40%.
[0053] This volume distribution can, on the one hand, prevent an increased tendency to cracking in the second building layer B2 and, on the other hand, limit the wear of the second building layer B2 while maintaining good friction values and low emission values.
[0054] Regardless of whether the second building layer B2 has embedded tungsten carbide particles W or embedded titanium carbide particles T, the second building layer B2 can also be advantageously alloyed with molybdenum. The alloying can be in the range of about 3 weight percent to 20 weight percent, preferably in the range of about 3 weight percent to 12 weight percent. Particularly preferably, the second building layer B2 is alloyed with molybdenum at a height of about 10 weight percent. In other words, the mass proportion of alloyed molybdenum in the total mass of the second building layer B2 can be in the range of about 3% to about 20%.
[0055] Now with the help of Figure 4 Explanation of the coating B (see Figure 3 ). The coating of the brake body 1 is preferably carried out by so-called high-speed laser deposition welding. For this purpose, the base body G of the brake body 1 is first oriented vertically with its rotation axis R, i.e. in the height direction Z, by means of a device not shown in detail, so that the flat side Fa is oriented with its flat extension F parallel to the horizontal direction Y.
[0056] The base body G, ie the uncoated brake disk, is previously produced according to conventional series production processes (not explained in detail).
[0057] The coating tool 3 is approximately parallel to the rotation axis R. The coating tool 3 can be moved uniaxially orthogonal to or radial to the rotation axis R and parallel to the horizontal direction Y. The coating tool has at least one laser optical device for generating a laser beam L and a nozzle for ejecting powdered coating material P1. At least one laser source (not shown) and at least one powder conveyor (not shown) are connected to the coating tool 3.
[0058] The substrate G is then set into rapid rotation so that it rotates at a specific speed n about the axis of rotation R. The coating of the substrate G begins at a radially inner position Gi and continues by a radial feed movement V in the direction of a radially outer position Ga of the substrate G.
[0059] Simultaneously with the generation of the laser beam L, the powder conveyor is operated in such a way that a powdered coating material P1 is conveyed with a specific powder mass flow m. The powdered coating material P1 consists of powder particles with a spherical, i.e., spherical, outer shape and has a material composition that corresponds to the first building layer B1 to be produced. Thus, the powdered coating material P1 contains components of an iron alloy (316L or 430L) and molybdenum.
[0060] Depending on the current position of the coating tool 3 , the rotation speed n of the base body G is adapted in order to achieve a constant thickness of the build-up layer B1 over the entire surface of the flat side Fa to be coated.
[0061] In the coating method, the radiation intensity of the laser beam L is adjusted in such a way that overheating of the structured layer B1 or B2 to be applied in each case does not occur.
[0062] In the coating method shown, the coating raw material (ie, the powdered coating material P1) is melted. For this purpose, the powdered coating material P1 is supplied in a targeted manner to the laser beam L, ie, the laser spot, which hits the base body G via the coating tool 3. There, the powdered coating material P1 melts and forms a molten pool SB.
[0063] In contrast, the base body G itself does not form a melt pool, but is only locally heated to a temperature slightly below its melting temperature. Therefore, unmelted particles of the powdered coating material P1 are not introduced into the melt of the base body G, but are deposited from particles of the powdered coating material P1 to form a melt pool SB. At the direct interface between the molten coating material (P1 in the image) and the locally intensified heated surface of the substrate (here the base body G), the coating material (here P1) is very well bonded to the substrate (here the base body G) by diffusion processes, without increased mixing of the materials involved.
[0064] Since the powdery coating material P1 is brought into the laser beam L in the direction of the gravitational acceleration g or approximately in the direction of the gravitational acceleration, the powdery coating material can stay in the laser beam L for as long as possible and thus can be melted well.
[0065] It should be mentioned here that during the coating process, the coating tool 3 is moved radially outwards with an advance movement v.
[0066] Furthermore, the feed movement v of the coating tool and the rotational speed of the brake body 1 are coordinated with one another in such a way that during a complete rotation of the brake body 1 through 360 degrees, a certain overlap of the coating path applied during the rotation occurs with the previously applied coating path.
[0067] When the first building layer B1 is applied in the desired manner to the base body G, the second building layer B2 is then applied in a corresponding manner to the surface O of the first building layer B1. A coating material P2 is then supplied which corresponds to the material composition of the second building layer B2 to be produced, i.e. has the components of an iron alloy (316L or 430L), tungsten carbide or titanium carbide and molybdenum.
[0068] The coating tool 3 is here again advanced radially from the inside to the outside in a similar manner to the first process step. However, for applying the second building layer B2 , a powdered second coating material P2 is now supplied to the laser beam L. The powdered second coating material P2 is preferably also present as powder particles with a spherical shape.
[0069] Reference numerals list
[0070] 1 brake body
[0071] 2 Brake calipers
[0072] 3. Cladding Tools
[0073] 10a, 10b friction ring
[0074] 11 Ventilated intermediate space
[0075] 12 Friction surface
[0076] 13 hub
[0077] A binding region
[0078] B coating
[0079] B1 First construction layer
[0080] B2 Second construction layer
[0081] d1 thickness
[0082] d2 thickness
[0083] d3 thickness
[0084] E Iron alloy matrix
[0085] F plane extension
[0086] Fa, Fb plane side
[0087] G matrix
[0088] Gi radial inner position
[0089] Ga radial outer position
[0090] g Gravity acceleration
[0091] KMotor Vehicle
[0092] LLaser beam
[0093] m powder mass flow
[0094] Speed
[0095] OSurface
[0096] P1 Powdered first coating material
[0097] P2 Powdered second coating material
[0098] RRotation axis
[0099] SB melt pool
[0100] Titanium carbide particles
[0101] V feed motion
[0102] WTungsten Carbide Particles
[0103] Y horizontal direction
[0104] Z height direction
Claims
1. A brake body (1) for a motor vehicle (K), comprising a base body (G) having at least partially flat surfaces, at least two build-up layers (B1, B2) being applied at least partially to the flat sides (Fa, Fb) of the base body, wherein: A surface is constructed by means of the building layers (B1, B2), which surface serves as a friction surface (12) for a brake lining when the brake body (1) is mounted on the motor vehicle (K), wherein a first building layer (B1) is present, which is adjacent to the base body (G), and a second building layer (B2) is present, which is applied to the first building layer (B1), wherein the second building layer (B2) consists of the following composite material, which consists of an iron alloy matrix (E) with embedded tungsten carbide particles (W) or with embedded titanium carbide particles (T), characterized in that at least the first building layer (B1) is an iron alloy that is alloyed with at least molybdenum in a range of 3 weight percent to 20 weight percent.
2. The brake body (1) according to claim 1, characterized in that The second build-up layer (B2) is also alloyed with at least molybdenum in a range of 3% by weight to 20% by weight.
3. The brake body (1) according to claim 1 or 2, characterized in that The volume ratio of the embedded tungsten carbide particles (W) to the volume ratio of the iron alloy matrix (E) is in the range of 10% to 20%.
4. The brake body (1) according to claim 1 or 2, characterized in that The volume ratio of the embedded titanium carbide particles (T) to the volume ratio of the iron alloy matrix (E) is in the range of 10% to 40%.
5. Braking body (1) according to any one of the preceding claims, characterized in that The iron alloy in the first building layer (B1) consists of austenitic stainless steel having material properties corresponding to material 1.4404 according to DIN EN 10027-2 or material 316L according to AISI.
6. Braking body (1) according to any one of the preceding claims 1 to 4, characterized in that The iron alloy of the first building layer ( B1 ) consists of a ferritic stainless steel having material properties corresponding to a 1.4016 material according to DIN EN 10027-2 or a 430L material according to AISI.
7. Braking body (1) according to any one of the preceding claims, characterized in that The first structured layer (B1) has a thickness (d1) in the range from 50 μm to 350 μm, viewed perpendicularly to the planar extension (F) of the planar sides (Fa, Fb).
8. Braking body (1) according to any one of the preceding claims, characterized in that The second structured layer (B2), viewed perpendicularly to the planar extension (F) of the planar sides (Fa, Fb), has a thickness (d2) in the range from 60 μm to 420 μm.
9. Braking body (1) according to any one of the preceding claims, characterized in that The iron alloy matrix (E) in the second building layer (B2) consists of a material having material properties corresponding to the 1.4404 material according to the EN 10027-2 standard or the 316L material according to the AISI standard.
10. Braking body (1) according to any one of the preceding claims 1 to 8, characterized in that The iron alloy matrix (E) in the second building layer (B2) consists of a material having material properties corresponding to a 1.4016 material according to DIN EN 10027-2 or a 430L material according to AISI.
Citation Information
Patent Citations
Brake components for a motor vehicle and methods for manufacturing a brake component
DE102021207133B3
Method for coating a cylinder barrel of a cylinder crankcase, cylinder crankcase with a coated cylinder barrel and engine
EP3325685B1